Decolorization potential of bacteria isolated from Sungai Lembing hot springs and Ganoderma lucidum on methyl red dye - Sharif, Mohd. Faez; Azizan, Nur Hafizah; Mohd Hafidz, Ismail Fitri (American Institute of Physics Inc., 2022)
Two bacteria strains isolated from Sungai Lembing hot springs, Pahang, Malaysia (Achromobacter marplatensis and Aquamicrobium defluvii) and a white-rot fungus (Ganoderma lucidum) were tested for their decolorization potential. The microbes were developed in minimal salt medium (MSM) supplemented with co-substrate (glucose) and 100 mg/L methyl red dye under ႏ and ႏ with agitation for the decolorization treatment. The dye decolorization rate was spectrophotometrically determined within 3 stipulated treatment days for both temperatures and the colour changes between those samples were observed. G. lucidum effectively decolorized methyl red dye with 64.14% and 33.01% at ႏ and ႏ, respectively. The other strains, Achromobacter marplatensis and Aquamicrobium defluvii were effective at 37ႏ with the decolorizing efficiency of 29.18% and 6.04%, respectively. Further comparative analysis of all metabolites and control through the FTIR spectral analysis depicted a slight change of functional groups of the methyl red dye, indicating the biodegradation activity of the samples. Thus, this study showed G. lucidum had higher potential for methyl red dye decolorization in both different temperatures compared to the hot springs’ bacteria, hence indicates its potential to be used in the industrial effluents’ treatment containing azo dye.